Metode Pembelajaran Klasikal Ilmu Sharf Pada Mahasiswa Pendidikan Bahasa Arab FITK UNSIQ Jawa Tengah - Ahmad Rois; Rufa Hindun Farhisiyati; Nurul Azizah; Farah Faida (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The purpose of this study is to describe Shorof learning using classical methods that are usually used in Islamic boarding schools. This research was carried out at the PBA FITK Unsiq Wonosobo study program. This research uses a type of field research with a qualitative approach. Data collection by means of interviews, observation and documentation. The research instrument is the researcher himself who makes guidelines in data collection. Data analysis using trianggulation. The results of the study produced findings related to supporting and inhibiting factors for the implementation of classical methods in learning Shorof science